Predictors of poor haematopoietic stem cell mobilisation in patients with haematological malignancies at a South African centre. (August 2022) - du Toit, Justin; Goeijenbier, Marco; du Toit, Cecile; de Witt, Pieter; Koornhof, Hannes; Oosthuizen, Jenna; Louw, Vernon Johan; Seftel, Matthew; Verburgh, Estelle
Abstract: Background: Autologous stem cell transplant (ASCT) is an established consolidation strategy in the treatment of haematological malignancies, however poor mobilisation (PM) can contribute to patient morbidity and high resource utilisation. Identifying the incidence, risk factors for PM and engraftment outcomes are important goals in our resource limited setting. Methods: We retrospectively analyzed patients with haematological malignancies that consecutively underwent ASCT at Groote Schuur hospital, Cape Town, South Africa from January 2013 to January 2019. Results: 146 patients – majority with multiple myeloma (MM)(41, 8%), F:M= 1:2, underwent leukapheresis with median age of 32 years (range, 9 – 66 years). PM occurred in 25/146 (17%), mobilisation failure (MF) in 3/146 (2%) and super mobilisation (SMs) in 99/146 (68%), respectively. Risk factors for PM were: diagnosis of acute leukaemia (RR = 25, 95% CI 3.4 – 183, p = 0.002) and Hodgkin lymphoma (RR = 19, 95% CI 2.6 – 142, p = 0.004); low white cell count (WCC) at harvest (WCC < 9 × 10 9 /L (RR=4.3, 95% CI 2.3 – 8.3, p < 0.0001) and two vs one line of prior therapy (RR = 3.1, 95% CI 1.45 – 6.7, p = 0.0037). Median days to neutrophil and platelet engraftment were 14 days (95% CI 14–15 days) and 16 days (95% CI 15–16 days) respectively. Conclusion: PM occurred in 17% of a contemporary South African ASCT cohort, albeit with a low MF rate (2%). There was surprisingly high rate (68%) of SMs, possibly reflective of superfluous mobilisation strategy in MM patients. We identified predictive factors for PM that will lead to enhanced cost-effective use of plerixafor.